Degradation Of Methylene Blue Using Ultrasonic Irradiation: A Comparison Of Ultrasound With And Without Salt (Sodium Chloride) - Patrick, Albrecht Raphael (2010)
In this research,the objectives are to determine the best conditions for the degradation of methylene blue and at the same time studying the effects of Sodium Chloride (NaCl) when added to a dye solution that being degraded via ultrasonic irradiation method.Environmental violations caused by poorly treated textile effluents have caused major problems towards aquatic life and the stability of the aquatic ecosystem in rivers or lakes.Methylene blue is a basic dye that is commonly used in textile industries. This research project is designed to degrade methylene blue using ultrasonic irradiation with and without the addition of salt by manipulating key parameters such as the temperature of the dye solution in the range of 40 oC – 80 oC, the initial concentration of dye samples at 4 mg/L - 20 mg/L, the time of for methylene blue to be degraded (15 minutes – 120 minutes) and the pH value (pH 1.61 – pH 12.35)of the dye solution while being degraded under ultrasonic irradiation. The results for the experiment showed that methylene blue is best degraded at 80oC, 4 mg/L and 90 minutes with the pH value of 12.35,where the percentage of degradation for the 100 ml dye solution was at 86.28%. When the experiment was repeated with the addition of salt (NaCl),to the solution was degraded at 87.80%.It can be concluded that the treatment of waste water containing methylene blue can be degraded by using ultrasonic irradiation and the efficiency of this method can be improved with the addition of salt into the methylene blue solution.